2015
DOI: 10.1038/ijo.2015.34
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin profiling reveals a role for haematopoietic prostaglandin D synthase in adipose tissue macrophage polarisation in mice and humans

Abstract: Background/ObjectivesObesity has been associated with both changes in adipose tissue lipid metabolism and inflammation. A key class of lipid-derived signalling molecules involved in inflammation are the prostaglandins. In this study we aimed to determine how obesity affects the levels of prostaglandins within white adipose tissue and determine which cells within adipose tissue produce them. To avoid the effects of cellular stress on prostaglandin levels we developed a multivariate-statistical approach in which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 49 publications
(69 reference statements)
4
26
0
1
Order By: Relevance
“…We also found that the tissue levels of PGE 2 were significantly reduced in obese mice. This is consistent with previous studies of HFD on adipose tissue levels of PGE 2 (). The biological significance of PGE 2 remains to be determined.…”
Section: Discussionsupporting
confidence: 93%
“…We also found that the tissue levels of PGE 2 were significantly reduced in obese mice. This is consistent with previous studies of HFD on adipose tissue levels of PGE 2 (). The biological significance of PGE 2 remains to be determined.…”
Section: Discussionsupporting
confidence: 93%
“…As a model for assessing whether PGD 2 itself is able to suppress inflammatory cell activation, we treated naïve or polarized bone marrow-derived macrophages (BMMs) in vitro with PGD 2. RNA-seq analysis of naïve BMMs treated with PGD 2 reveals induction of anti-oxidant genes and, as previously reported, a shift towards an anti-inflammatory macrophage phenotype (Figure S13A-B) (40). Lipopolysaccharide (LPS) induces a strong pro-inflammatory response in macrophages ( Figure S13C), and subsequent treatment with PGD 2 resulted in 322 genes being differentially expressed between control and LPS/PGD 2 -treated BMM ( Figure S13D, File S4).…”
Section: Pgd 2 Restrains Disease Progression By Promoting Environmentsupporting
confidence: 84%
“…HDL has antioxidant and anti-inflammatory properties 40 . Prostaglandin D2 is another eicosanoid produced in macrophages that promotes M2 differentiation and is positively correlated with insulin sensitivity 41 .…”
Section: Macrophage Functions In Lean Tissuementioning
confidence: 99%